2008
DOI: 10.1208/s12249-008-9143-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Solid-State Characterization of Inclusion Complexes Formed Between Miconazole and Methyl-β-Cyclodextrin

Abstract: Abstract. The aim of this study is to confirm the formation of inclusion complexes between miconazole (MCZ) and two derivatives of beta-cyclodextrin, methyl-beta-cyclodextrin (MβCD) and 2-hydroxypropyl-beta-cyclodextrin (HPβCD) in aqueous solution by phase solubility studies. Inclusion complexes with MβCD in the solid state were then prepared by different methods, i.e., kneading, coevaporation (COE), spray-drying (SD), and lyophilization (LPh). The physicochemical properties of these complexes were subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 30 publications
4
36
0
2
Order By: Relevance
“…6b, b1) is observed as cylindrical spheres. Both structures were in accordance with previous data (28,29). On the other hand, images related to inclusion complex (Fig.…”
Section: Scanning Electron Microscopysupporting
confidence: 92%
“…6b, b1) is observed as cylindrical spheres. Both structures were in accordance with previous data (28,29). On the other hand, images related to inclusion complex (Fig.…”
Section: Scanning Electron Microscopysupporting
confidence: 92%
“…Powder X-ray diffraction (PXRD) is the commonly used method for the detection of CD complexation either in the powder and microcrystalline states [ 12 ]. The PXRD profiles of the crystalline and non-crystalline RALA-αCD complexes are shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] The drug/CyD complexes are prepared by various methods and a lot of studies have been reported so far, e.g., kneading, coevaporation, freeze drying, solubility and spray drying methods, etc. [5][6][7] In addition, it has been demonstrated that the preparation methods or the preparation conditions can significantly influence the characteristics of the resulting complexes. [8][9][10] Al-Marzouqi et al reported that benzocaine/b-CyD complexes prepared by the supercritical fluid technology, kneading, co-evaporation, co-grinding or sealedheating methods had different physicochemical properties.…”
mentioning
confidence: 99%